A Rhetorical Analysis of Patriotism in American Independence Speeches - Nahawand Muhsin Hachim; prof.dr Mazin Jasim Mohammed Al-Hilu (Journal of College of Education, 2026)
This paper conducts a rhetorical analysis of patriotic language in American Independence Day speeches to explore presidential methods of building patriotic sentiment through words. Historical investigations of these speeches exist, but research on their rhetorical elements of patriotic language remains insufficient. The study investigates rhetorical devices which generate patriotic emotions while building national unity through language that reflects historical periods. The research adopts a qualitative method to evaluate two presidential Independence Day speeches delivered by Donald Trump (2019 Republican) and Barack Obama (2016 Democrat) through Leech’s (1969) rhetorical device framework. Presidents use complex rhetorical strategies, which include metaphor and repetition alongside parallelism amplification, antithesis, negation, and hyperbole, to convert historical anniversaries into active patriotic feelings. The most important findings that study found is the fact that rhetorical means are not used indiscriminately in the discourses of events such as Independence Day in particular, but are the linguist strategically employed to achieve goals including national feeling and strengthening national unity. As for the tools used for both speeches, metaphor and repetition were commonly used to achieve emotional interaction. All of this indicates the process of transforming the historical anniversary into an effective national identity among the citizens.